2016
DOI: 10.1521/aeap.2016.28.4.312
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Condom Use Over Time Among Female Sex Workers and Their Male Noncommercial Partners and Clients

Abstract: Female sex workers (FSWs) often report inconsistent condom use with clients and noncommercial male partners, yet changes in condom use with various partner types during participation in observation studies remains underexplored. This longitudinal study of 214 FSWs and their male, noncommercial partners in the Mexico-U.S. border region, where HIV prevalence among FSWs continues to be high, utilized negative binomial regressions to examine changes in condom use with intimate partners and clients (regular and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Several studies have concluded that inconsistent condom use can contribute to the spread of STIs [5][6][7]. A systematic review and meta-analysis performed among female sex workers (FSW) globally reported 19.1% (95% CI: 1.7 to 36.4) engaged in unprotected vaginal sex and 46.4% (95% CI: 9.1 to 83.6) engaged in unprotected anal sex [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have concluded that inconsistent condom use can contribute to the spread of STIs [5][6][7]. A systematic review and meta-analysis performed among female sex workers (FSW) globally reported 19.1% (95% CI: 1.7 to 36.4) engaged in unprotected vaginal sex and 46.4% (95% CI: 9.1 to 83.6) engaged in unprotected anal sex [8].…”
Section: Introductionmentioning
confidence: 99%
“…We also noted that PrEP use was higher among married / cohabiting FSWs as well as those who reported to be separated/divorced/widowed. Findings from other studies have reported that primary HIV risk for FSWs is likely to be from their main/regular partners rather than their clients because of the low condom use with the former (38,(47)(48)(49)(50). Therefore, findings from our study could possibly reflect the utility of PrEP in relationships where females are unable to negotiate condom use and in the likely event that their spouse/ main partner also has other sexual partners.…”
Section: Discussionmentioning
confidence: 65%
“…However, these studies did not specify if these were observed in regular or non-regular partnerships which is an important distinction for women at high HIV risk such as those in this study [14] [23,24]. Low condom use with regular partners among women at high HIV risk has been extensively reported in previous literature [8,11,[25][26][27] [28]. In one such study by Lowndes et in Benin [29], it was shown that a greater percentage of FSW's regular partners were HIV positive compared to their nonregular partners (16.1% vs. 8.5%).Therefore, given the multiple and concurrent partnerships among women in these high risk populations, unprotected sex with regular partners may represent their greatest risk of HIV infection.…”
Section: Plos Onementioning
confidence: 90%